Primary torsion of vermiform appendix mimicking acute appendicitis - Marsdin, Emma L (BMJ Publishing Group, 2011)
Acute appendicitis is a common condition, 8% of the developed world have an appendicectomy in their lifetime. However, torsion of the appendix is a rare disorder first described in 1918 presenting in a manner undistinguishable from acute appendicitis. The authors describe a case of a 48-year-old man who presented with a short history consistent with acute appendicitis. At open appendicectomy, was found to have an acute clockwise torsion of the vermiform appendix at a point 0.5 cm from its base. Histological examination of the specimen was consistent with torsion of the appendix but no underlying cause for the torsion was identified. The postoperative recovery was uneventful; the patient received intravenous antibiotics for a further 48 h and was discharged home without any complications.